Experimental investigation and optimization of abrasive water jet drilling parameters for CF/PEEK thermoplastic composites - Yakut, Necdet; Cakir, Orhan (SAGE PUBLICATIONS LTD, 2026)
Abrasive water jet (AWJ) drilling is a thermally benign method enabling damage-tolerant hole production in recyclable carbon fiber-reinforced polyetheretherketone (CF/PEEK) laminates. Using a Taguchi L18 orthogonal array, this study investigated the effects of traverse rate, water-jet pressure, and abrasive mass flow rate on surface roughness (Ra), kerf angle (theta), dimensional deviation (Delta D), and entry/exit delamination factors (Fd). To link process conditions with surface morphology, grey relational analysis (GRA) was integrated with the Taguchi method for multi-response optimization. The analysis revealed that damage mechanisms fundamentally evolve with traverse rate; lower speeds cause interlaminar delamination due to prolonged hydraulic loading, whereas higher speeds shift the damage to localized fiber fracture and erosion. Notably, entry-side delamination was consistently more severe than at the exit. The optimum parameter combination to minimize all defects simultaneously was identified as 1250 mm/min traverse rate, 2000 bar jet pressure, and 350 g/min abrasive mass flow rate. ANOVA confirmed traverse rate as the most dominant factor, contributing approximately 60% to the overall hole quality. Ultimately, this study establishes a robust process window for dimensionally accurate, low-damage AWJ drilling of CF/PEEK composites, highlighting the critical role of traverse speed in governing microscale damage transitions.
Keywords: abrasive water jet drilling; CF/PEEK; process optimization; delamination; kerf angle; dimensional accuracy; INDUCED DAMAGE; TECHNOLOGIES; PERFORMANCE; EVOLUTION; SURFACES; Materials Science; Polymer Science